Core of sensory gating deficits in first-episode schizophrenia: attention dysfunction - Ding, Yushen; Tian, Qing; Hou, Wenpeng; Chen, Zhenzhu; Mao, Zhen; Bo, Qijing; Dong, Fang; Wang, Chuanyue (Frontiers in Psychiatry, 2023)
Background Sensory gating deficits are a common feature of schizophrenia and may be indicative of higher-order psychopathological impairments. It has been proposed that incorporating subjective attention components into prepulse inhibition (PPI) measures may improve the accuracy of assessing these deficits. This study aimed to investigate the relationship between modified PPI and cognitive function, with a specific focus on subjective attention, to gain a better understanding of the underlying mechanisms of sensory processing deficits in schizophrenia. Methods Fifty-four unmedicated first-episode schizophrenia (UMFE) patients and 53 healthy controls participated in this study. The modified Prepulse Inhibition paradigm, including Perceived Spatial Separation PPI (PSSPPI) and Perceived Spatial Colocation PPI (PSCPPI), was used to evaluate sensorimotor gating deficits. Cognitive function was assessed in all participants using the Chinese version of the MATRICS Consensus Cognitive Suite Test (MCCB). Results UMFE patients had lower MCCB scores and deficient PSSPPI scores than healthy controls. PSSPPI was negatively correlated with total PANSS scores and positively correlated with the speed of processing, attention/ vigilance, and social cognition. Multiple linear regression analysis showed that the PSSPPI at 60 ms had a significant effect on attentional/ vigilance and social cognition, even after controlling for gender, age, years of education, and smoking. Conclusion The study revealed notable impairments in sensory gating and cognitive function in UMFE patients, best reflected by the PSSPPI measure. Specifically, PSSPPI at 60 ms was significantly associated with both clinical symptoms and cognitive performance, suggesting that PSSPPI at 60 ms may capture psychopathological symptoms related to psychosis.